18TiPDESIGN OF A PHASE 2 STUDY OF BRENTUXIMAB VEDOTIN (SGN-35) AS SALVAGE THERAPY FOR MALES WITH CHEMORESISTANT GERM-CELL TUMORS (GCT). (November 2014) - Giannatempo, P.; Anichini, A.; Raggi, D.; Cordareschi, E.; Nicolai, N.; Colecchia, M.; Salvioni, R.; Valagussa, P.; Gianni, A.; Necchi, A.
Abstract : Background : Complete responses with third-line or later salvage chemotherapy (CT) for GCT range from 5% to 10%, and nearly all patients (pts) progressing after high-dose CT will ultimately die. CD30 is expressed by embryonal carcinoma (ECA) thus lending support to a rationale for a targeted approach. SGN-35 is an antibody-drug conjugate consisting of the chimeric anti-CD30 antibody SGN-30 chemically conjugated to an antitubulin synthetic analog. The primary objective of the study will be the activity of SGN35 in refractory GCT. Trial design : 24 pts with biopsy-proven CD30+ GCT will receive intravenous SGN35 at the dose of 1.8 mg/Kg every 3 weeks until disease progression or onset of unacceptable toxicity. Further eligibility requirements will include failure of 2 or 3 platinum-based CT (including HDCT). All pts will undergo measurement of serum tumor markers, a computed tomography and a PET scan q6 weeks. An optimal Simon's 2-stage design will be applied. The primary endpoint is the objective response-rate (ORR). An ORR of 5% is not promising, while a 25% rate will be promising. In stage 1, 9 evaluable patients will be accrued. If ≥1 patient will be responding, enrollment will be extended to the 2nd stage for further 15. If, over the total of 24 stage 1 plus stage 2 pts, 3 at least will be responding, treatment will be declared worthy for further investigations. The type I and II error are set both at 0.1 (power = 90%). We will test the hypothesis that brentuximab can promote anti-tumor immunity, which might contribute to the clinical efficacy. We will use multiparametric flow cytometry to assess whether SGN-35 can: a) impact on frequency and absolute counts of all main cellular subsets; b) shift the TH1/TH2 balance, in favor of a TH1-type of response; c) reduce the frequency of circulating CD30 + regulatory T cells and CD30 + TH2 memory T cells; d) promote an increase in circulating CD161 + TH17 T cells; d) reverse the condition of immune dysfunction, by assessing the expression of negative co-signaling molecules (PD-1, CTLA-4, CD160, CD244, CD57, TIM-3, LAG-3) and of activation/proliferation markers (Ki67, GranzymeB, CD69) on main T cell subsets. As of July 2014, 6 pts have been enrolled (NCT01851200). Disclosure : All authors have declared no conflicts of interest.